Lokakarya Pembelajaran II 2023: Mewujudkan Pendidikan yang Berkualitas dengan P5 - Elfiadi; Burhanuddin; Intan, Cut; Wali, Muhammad (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Community service activities aim to improve understanding and implementation of the Pancasila “P5” Student Profile Consolidation Project; and independent research program at Lhokseumawe City. Involving teachers, supervisors and principals from different educational institutions, the program includes preparation, implementation, evaluation, and monitoring phases. The support team of the Generation III driving school has planned intensive training and prepared comprehensive educational materials, including the purchase of necessary equipment. Implementation involves participants in trainings, discussions, workshops, and practices, enabling them to apply P5 and the Merdeka curriculum in everyday learning contexts. Evaluation results showed increased participants' understanding and confidence in applying the concept. Monitoring includes the development of supplementary materials, ongoing training, and monitoring of P5 implementation. This program has a positive impact on participants, preparing them for P5 and the Merdeka program. Ongoing collaboration between the Class III driving school support team and participating educational institutions will ensure continuous improvement in the quality of education in Lhokseumawe City.